Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Fredrick J. Rich (1951–2025): palynologist, coal geologist, naturalist, and teacher - David T. Pocknall; James C. Hower; Robert K. Booth; Jennifer M.K O’Keefe (Palynology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Chemical emissions from offshore wind farms: From identification to challenges in impact assessment and regulation - Elena Hengstmann; Pablo Zapata Corella; Katharina Alter; Maria J. Belzunce-Segarra; Andy M. Booth; Javier Castro-Jiménez; Niklas Czerner; Karien De Cauwer; Geneviève Deviller; Alessio Gomiero; Nils Goseberg; Simone Hasenbein; et al. (Marine Pollution Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Chow diet in mouse aging studies: nothing regular about it - Jennifer Lee; Chloe Purello; Sarah L. Booth; Brian Bennett; Christopher D. Wiley; Ron Korstanje (GeroScience, 2023)
Chow diet is used in the majority of rodent studies and, although assumed to be standardized for dietary source and nutritional contents, it varies widely across commercial formulations. Similarly, current approaches to study aging in rodents involve a single-diet formulation across the lifespan and overlook age-specific nutritional requirements, which may have long-term effects on aging processes. Together, these nutrition-based disparities represent major gaps in geroscience research, affecting the interpretation and reproducibility of the studies. This perspective aims to raise awareness on the importance of rodent diet formulation and proposes that geroscientists include detailed descriptions of all experimental diets and feeding protocols. Detailed reporting of diets will enhance rigor and reproducibility of aging rodent studies and lead to more translational outcomes in geroscience research.

Shifting the social determinants of food insecurity during the COVID-19 pandemic: the Australian experience - Christina Zorbas; Jennifer Browne; Alexandra Chung; Anna Peeters; Sue Booth; Christina Pollard; Steven Allender; Anna Isaacs; Corinna Hawkes; Kathryn Backholer (Food Security, 2023)
We aimed to explore experiences of government-led actions on the social determinants of food insecurity during Australia’s COVID-19 pandemic response (which included novel, yet temporary, social protection measures to support Australians facing hardship during state-wide lockdowns). During November–December 2020, we conducted in-depth interviews with 24 Victorians who received government income support (prior to COVID-19) and the temporary COVID-19 specific payments. Interviews were guided by a theoretical understanding of the social determinants of health and health inequities, which we aligned to the social policy context. Data were audio-recorded, transcribed, inductively coded, categorised and thematically analysed. Our sample included mostly women (n = 19) and single parents (n = 13). Interviews reflected four key themes. Firstly, participants described ‘battles all around them' (i.e., competing financial, health and social stressors) that were not alleviated by temporary social policy changes and made healthy eating difficult to prioritise during the pandemic. Secondly, housing, income, job, and education priorities rendered food a lower and more flexible financial priority – even with 18 participants receiving temporary income increases from COVID-19 Supplements. Thirdly, given that food remained a lower and more flexible financial priority, families continued to purchase the cheapest and most affordable options (typically less healthful, more markedly price discounted). Finally, participants perceived the dominant public and policy rhetoric around income support policies and healthy eating to be inaccurate and shaming – often misrepresenting their lived experiences, both prior to and during COVID-19. Participants reported entrenched struggles with being able to afford basic living costs in a dignified manner during COVID-19, despite temporary social protection policy changes. To reduce inequities in population diets, a pre-requisite to health, all stakeholders must recognise an ongoing responsibility for adopting long-term food and social policies that genuinely improve lived experiences of food insecurity and poverty.

Physiological factors facilitating the persistence of Pocillopora aliciae and Plesiastrea versipora in temperate reefs of south-eastern Australia under ocean warming - Raúl A. González-Pech; David J. Hughes; Paige Strudwick; Brett M. Lewis; David J. Booth; Will F. Figueira; Brigitte Sommer; David J. Suggett; Jennifer Matthews (Coral Reefs, 2022)
High-latitude reefs are suboptimal coral habitats, but such habitats are increasingly considered to be potential refugia from climate change for range-shifting coral reef species. Notably, tropical reef fish have been observed along the south-east coast of Australia, but their establishment on temperate rocky reefs is currently limited by winter minimum temperatures and other resource needs, such as structurally complex habitats typical of tropical reefs. Recent expansion of the branching subtropical coral Pocillopora aliciae in rocky reefs near Sydney (34° S) could diversify the architectural structure of temperate marine environments, thereby providing potential shelter for tropical reef taxa in warming seas. Here, we investigated whether future environmental conditions ( i.e. temperature increase) can influence the dominance of the subtropical branching coral P. aliciae over the resident encrusting coral Plesiastrea versipora in coastal Sydney by characterising physiological ( e.g. metabolic stability) and behavioural ( e.g. interspecific competitive hierarchy) traits that contribute to their competitive fitness. Our results suggest that a metabolic response, mediated by sterol and lipid metabolic pathways and provision of antioxidants, allows P. aliciae to reduce cellular stress and withstand exposure to short-term increased temperature. Conversely, P. versipora was more susceptible to heat exposure with no metabolic mediation observed. While P. versipora displayed greater aggressive behaviour when in direct contact with P. aliciae under all temperature conditions, the superior physiological and metabolic flexibility under increased temperatures of P. aliciae suggests that this species will likely outperform P. versipora under future increased temperatures. Such contrasting responses to environmental change would facilitate shifts in coral community and functional composition that could support further tropicalisation of coastal New South Wales.

The Future of Midlatitude Cyclones - Jennifer L. Catto; Duncan Ackerley; James F. Booth; Adrian J. Champion; Brian A. Colle; Stephan Pfahl; Joaquim G. Pinto; Julian F. Quinting; Christian Seiler (Current Climate Change Reports, 2019)
Purpose of Review This review brings together recent research on the structure, characteristics, dynamics, and impacts of extratropical cyclones in the future. It draws on research using idealized models and complex climate simulations, to evaluate what is known and unknown about these future changes. Recent Findings There are interacting processes that contribute to the uncertainties in future extratropical cyclone changes, e.g., changes in the horizontal and vertical structure of the atmosphere and increasing moisture content due to rising temperatures. Summary While precipitation intensity will most likely increase, along with associated increased latent heating, it is unclear to what extent and for which particular climate conditions this will feedback to increase the intensity of the cyclones. Future research could focus on bridging the gap between idealized models and complex climate models, as well as better understanding of the regional impacts of future changes in extratropical cyclones.

Temperature influences habitat preference of coral reef fishes: Will generalists become more specialised in a warming ocean? - Paloma A. Matis; Jennifer M. Donelson; Stephen Bush; Rebecca J. Fox; David J. Booth (Global Change Biology, 2018)
Climate change is expected to pose a significant risk to species that exhibit strong behavioural preferences for specific habitat types, with generalist species assumed to be less vulnerable. In this study, we conducted habitat choice experiments to determine how water temperature influences habitat preference for three common species of coral reef damselfish (Pomacentridae) that differ in their levels of habitat specialisation. The lemon damselfish Pomacentrus moluccensis , a habitat specialist, consistently selected complex coral habitat across all temperature treatments (selected based on local average seasonal temperatures naturally experienced in situ: ambient winter 22°C; ambient summer 28°C; and elevated 31°C). Unexpectedly, the neon damselfish Pomacentrus coelestis and scissortail sergeant Abudefduf sexfasciatus , both of which have more generalist habitat associations, developed strong habitat preferences (for complex coral and boulder habitat, respectively) at the elevated temperature treatment (31°C) compared to no single preferred habitat at 22°C or 28°C. The observed shifts in habitat preference with temperature suggest that we may be currently underestimating the vulnerability of some habitat generalists to climate change and highlight that the ongoing loss of complex live coral through coral bleaching could further exacerbate resource overlap and species competition in ways not currently considered in climate change models.

‘Stick with your own kind, or hang with the locals?’ Implications of shoaling strategy for tropical reef fish on a range‐expansion frontline - Shannen M. Smith; Rebecca J. Fox; David J. Booth; Jennifer M. Donelson (Global Change Biology, 2018)
Range shifts of tropical marine species to temperate latitudes are predicted to increase as a consequence of climate change. To date, the research focus on climate‐mediated range shifts has been predominately dealt with the physiological capacity of tropical species to cope with the thermal challenges imposed by temperate latitudes. Behavioural traits of individuals in the novel temperate environment have not previously been investigated, however, they are also likely to play a key role in determining the establishment success of individual species at the range‐expansion forefront. The aim of this study was to investigate the effect of shoaling strategy on the performance of juvenile tropical reef fishes that recruit annually to temperate waters off the south east coast of Australia. Specifically, we compared body‐size distributions and the seasonal decline in abundance through time of juvenile tropical fishes that shoaled with native temperate species (‘mixed’ shoals) to those that shoaled only with conspecifics (as would be the case in their tropical range). We found that shoaling with temperate native species benefitted juvenile tropical reef fishes, with individuals in ‘mixed’ shoals attaining larger body‐sizes over the season than those in ‘tropical‐only’ shoals. This benefit in terms of population body‐size distributions was accompanied by greater social cohesion of ‘mixed’ shoals across the season. Our results highlight the impact that sociality and behavioural plasticity are likely to play in determining the impact on native fish communities of climate‐induced range expansion of coral reef fishes.

Lithium carbonate in the management of cannabis withdrawal: a randomized placebo-controlled trial in an inpatient setting - Jennifer Johnston; Nicholas Lintzeris; David J. Allsop; Anastasia Suraev; Jessica Booth; Dean S. Carson; David Helliwell; Adam Winstock; Iain S. McGregor (Psychopharmacology, 2014)

Drought as a Trigger for Rapid State Shifts in Kettle Ecosystems: Implications for Ecosystem Responses to Climate Change - Alex W. Ireland; Robert K. Booth; Sara C. Hotchkiss; Jennifer E. Schmitz (Wetlands, 2012)

Preparing for climate change in Washington State - Lara C. Whitely Binder; Jennifer Krencicki Barcelos; Derek B. Booth; Meriel Darzen; Marketa McGuire Elsner; Richard Fenske; Thomas F. Graham; Alan F. Hamlet; John Hodges-Howell; J. Elizabeth Jackson; Catherine Karr; Patrick W. Keys; et al. (Climatic Change, 2010)

Malaria severity and human nitric oxide synthase type 2 (NOS2) promoter haplotypes - Marc C. Levesque; Maurine R. Hobbs; Charles W. O’Loughlin; Jennifer A. Chancellor; Youwei Chen; Ariana N. Tkachuk; Jennifer Booth; Kistie B. Patch; Sallie Allgood; Ann R. Pole; Carolyn A. Fernandez; Esther D. Mwaikambo; et al. (Human Genetics, 2010)

Epac activation, altered calcium homeostasis and ventricular arrhythmogenesis in the murine heart - Sandeep S. Hothi; Iman S. Gurung; Jennifer C. Heathcote; Yanmin Zhang; Stephen W. Booth; Jeremy N. Skepper; Andrew A. Grace; Christopher L.-H. Huang (Pflügers Archiv - European Journal of Physiology, 2008)